Analysis of The Effect Financial Ratios as Basis For Measuring Financial Performance in Bank Syariah Indonesia - Nadiyah Yusriyyah; Rahmawati Khoiriyah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam Syarifuddin Lumajang, 2024)
Bank Syariah Indonesia was formed through the consolidation of PT Bank BRIsyariah Tbk, PT Bank Syariah Mandiri, and PT Bank BNI Syariah. Bank Syariah Indonesia aims to establish a sharia-compliant bank that will be a source of national pride, stimulate economic growth, and enhance the well-being of the broader community. The funds originate from the revenue generated by the profit sharing mechanism. The presence of several rivals and the prevailing economic uncertainties in Indonesia contribute to the instability observed in the banking sector. Hence, it is imperative to evaluate the financial performance of Bank Rakyat Indonesia Syariah by employing ratio analysis to analyze its financial performance. This study use computations generated from financial statement data. The tests employed include classical assumption tests, multiple linear analysis research models, and simultaneous tests for coefficients of determination. The findings indicated a partial impact on the Current Ratio.